Purine metabolism in Acholeplasma laidlawii B: novel PPi-dependent nucleoside kinase activity. - Tryon, V V (1984)
Acholeplasma laidlawii B-PG9 was examined for 16 cytoplasmic enzymes with activity for purine salvage and interconversion. Phosphoribosyltransferase activities for adenine, guanine, xanthine, and hypoxanthine were shown. Adenine, guanine, xanthine, and hypoxanthine were ribosylated to their nucleoside. Adenosine, inosine, xanthosine, and guanosine were converted to their base. No ATP-dependent phosphorylation of nucleosides to mononucleotides was found. However, PPi-dependent phosphorylation of adenosine, inosine, and guanosine to AMP, inosine monophosphate, and GMP, respectively, was detected. Nucleotidase activity for AMP, inosine monophosphate, xanthosine monophosphate, and GMP was also found. Interconversion of GMP to AMP was detected. Enzyme activities for the interconversion of AMP to GMP were not detected. Therefore, A. laidlawii B-PG9 cannot synthesize guanylates from adenylates or inosinates. De novo synthesis of purines was not detected. This study demonstrates that A. laidlawii B-PG9 has the enzyme activities for the salvage and limited interconversion of purines and, except for purine nucleoside kinase activity, is similar to Mycoplasma mycoides subsp. mycoides. This is the first report of a PPi-dependent nucleoside kinase activity in any organism.